Electrolyte, electrochemical device and electronic device

By using electrolytes of lithium difluorosulfonimide and fluorochemical compounds in lithium-ion batteries, a stable microchemical structure is formed, which solves the problem of degradation of high-temperature storage performance and batch cycle performance of lithium-ion batteries during the cycle process, and achieves better electrochemical performance.

CN119518100APending Publication Date: 2025-02-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411764394.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Lithium-ion batteries produce gas at high temperature during circulation, and the electrochemical interface film on the surface of the positive electrode sheet is easily damaged, resulting in a degradation of high-temperature storage performance and intermittent circulation performance.

Method used

An electrolyte solution including lithium difluorosulfonimide and fluoro compound is used to regulate the mass percentage content of lithium difluorosulfonimide and fluorochemical in the electrolyte solution to form a stable microchemical structure, promote the formation of a dense and thin positive electrode solid electrolyte interface film on the surface of the positive electrode active material, and reduce the hydrogen fluoride gas generated by side reactions.

Benefits of technology

It effectively reduces the content of hydrogen fluoride gas formed by side reactions at the positive electrode interface, reduces the thickness expansion of the electrochemical device, and improves the high-temperature storage performance and low-temperature batch circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168675560000221
    Figure BDA0005168675560000221
  • Figure BDA0005168675560000231
    Figure BDA0005168675560000231
  • Figure BDA0005168675560000251
    Figure BDA0005168675560000251
Patent Text Reader

Abstract

The invention provides an electrolyte, an electrochemical device and an electronic device, the electrolyte comprises lithium bis (fluorosulfonyl) imide and a fluorinated compound, based on the mass of the electrolyte, the mass percentage content of the lithium bis (fluorosulfonyl) imide is A%, the mass percentage content of the fluorinated compound is B%, 0.3 < = A < = 2, and 0.5 < = B < = 2.5. Through the arrangement, the content of hydrogen fluoride gas formed by interface lithium hexafluorophosphate is reduced, the thickness expansion of the electrochemical device is reduced, and the high-temperature storage performance and the low-temperature intermittent cycle performance of the electrochemical device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art

[0002] Electrochemical devices (such as lithium-ion batteries) are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has higher and higher requirements for the safety and cycle performance of lithium-ion batteries.

[0003] During the cycle process, lithium-ion batteries produce gas at high temperatures, and the electrochemical interface (CEI) film on the surface of the positive electrode is easily damaged, which affects the high-temperature storage performance and intermittent cycle performance of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide an electrolyte, an electrochemical device and an electronic device to improve the high-temperature storage performance and low-temperature intermittent cycle performance of the electrochemical device.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides an electrolyte, which includes lithium bis(fluorosulfonyl)imide and a fluorinated compound. Based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the fluorinated compound is B%, 0.3≤A≤2, 0.5≤B≤2.5; preferably, 0.45≤A≤1.2, 1.2≤B≤2.0. The bis(fluorosulfonyl)imide anion (FSI) in the electrolyte is - Anions) and fluorinated compounds can form a stable microscopic chemical structure with the highest occupied molecular orbital (high HOMO orbital energy level). When the value of A and the value of B are regulated within the scope of the present application, a relatively dense and thin positive electrode solid electrolyte interface film (CEI film) can be formed at a uniform rate on the surface of the positive electrode active material during the charge and discharge process of the electrochemical device. This structure can reduce the content of hydrogen fluoride gas formed by side reactions at the positive electrode interface and reduce the thickness expansion of the electrochemical device, thereby improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0007] In some embodiments of the present application, 0.12≤A / B≤2.0. When the electrolyte includes lithium bis(fluorosulfonyl)imide and a fluorinated compound and satisfies the value of B / A within the range of the present application, the thickness expansion of the electrochemical device can be further reduced, and the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device can be improved.

[0008] In some embodiments of the present application, the electrolyte further comprises a dinitrile compound and a trinitrile compound. Based on the mass of the electrolyte, the mass percentage of the dinitrile compound is C%, the mass percentage of the trinitrile compound is D%, 1.53≤C / D≤2.4, 1.50≤D≤2.35. The dinitrile compound is a compound containing two cyano groups, and the trinitrile compound is a compound containing three cyano groups. When the electrolyte comprises the dinitrile compound and the trinitrile compound, and satisfies the values ​​of C / D and D within the scope of the present application, the dinitrile compound and the trinitrile compound will produce a certain synergistic effect within the scope. Due to the different electron cloud distributions of the dinitrile compound and the trinitrile compound structures, it is beneficial to form a relatively uniform CEI film on the surface of the positive electrode sheet. The combination of the two makes the CEI film have a variety of chemical properties and a certain chemical reaction inertness, thereby reducing the occurrence of chemical side reactions in the electrolyte and reducing the generation of by-products; on the other hand, it is beneficial to improve the voltage drop of the electrochemical device at high temperature and improve the structural stability of the electrochemical device at high temperature, thereby further improving the safety performance while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0009] In some embodiments of the present application, the electrolyte further includes propyl propionate, and the mass percentage of propyl propionate is 32% to 39% based on the mass of the electrolyte. When the electrolyte includes propyl propionate and the mass percentage of propyl propionate is within the range of the present application, the risk of increasing the AC impedance value of the electrochemical device under high temperature conditions can be reduced, and propyl propionate contributes to FSI. - Anions and fluorinated compounds form a more uniform LiF-containing negative electrode solid electrolyte membrane (SEI membrane) at the negative electrode interface. This structure has a good stabilizing function of reducing the formation of lithium dendrites, which can effectively reduce the generation of acidic gases during the cycle, thereby improving the high-temperature storage performance, low-temperature intermittent cycle performance and safety performance of the electrochemical device.

[0010] In some embodiments of the present application, the fluorinated compound includes fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-carbonate. At least one of ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate or 4,4-difluoro-5,5-dimethylethylene carbonate; preferably, the fluorinated compound includes at least one of fluoroethylene carbonate or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. By selecting fluorinated compounds within the above-mentioned range, the electrolyte can have a lower viscosity and a higher lithium ion conductivity, which is beneficial to the migration of ions in the electrolyte; at the same time, it is more conducive to the formation of a stable and relatively uniform SEI film at the interface between the negative electrode plate and the electrolyte, further reducing the side reactions of the electrolyte, reducing the gas production at the interface, making the positive electrode interface and the negative electrode interface have better interface stability, reducing the influence of gas molecules on the positive electrode interface and the negative electrode interface, thereby improving the low-temperature intermittent cycle performance and high-temperature storage performance of the electrochemical device.

[0011] In some embodiments of the present application, the electrolyte further includes 4-isopropylphenyl diphenyl phosphate, and the mass percentage of 4-isopropylphenyl diphenyl phosphate is M%, 1.5≤M≤4.5 based on the mass of the electrolyte. When the electrolyte includes 4-isopropylphenyl diphenyl phosphate and the value of M is within the range of the present application, it is beneficial to form a denser and more uniform SEI film at the negative electrode interface, reduce the solvent decomposition of the electrolyte during the reduction process, and reduce the risk of lithium dendrites deposited on the surface of the negative electrode, thereby further improving the high temperature storage performance, low temperature intermittent cycle performance and safety performance of the electrochemical device.

[0012] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte in any of the above embodiments. The electrochemical device of the present application has good high-temperature storage performance, low-temperature intermittent cycle performance, low-temperature rate performance, and safety performance.

[0013] In some embodiments of the present application, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the specific surface area of ​​the positive electrode active material is 0.3 m 2 / g to 0.4m 2 / g. By regulating the specific surface area of ​​the positive electrode active material within the above range, the positive electrode sheet has an active surface area and mechanical strength adapted to the electrolyte of the present application, while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device, the low temperature rate performance, extrusion test pass rate and hot box test pass rate of the electrochemical device can be effectively improved, and the high temperature anti-extrusion performance and hot box safety performance of the electrochemical device are improved, thereby improving the safety performance of the electrochemical device.

[0014] In some embodiments of the present application, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a first compound, the first compound includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate, based on the mass of the positive electrode material layer, the mass percentage of the first compound is F ppm, and the surface density of the positive electrode material layer is E mg / cm 2 , 93≤F / E≤560, 500≤F≤2800; preferably, 185≤F / E≤560. By regulating the values ​​of F / E and F within the above range, the positive electrode sheet has good wetting characteristics adapted to the electrolyte of the present application, and the positive electrode sheet and the electrolyte work synergistically, while taking into account the high-temperature storage performance and low-temperature intermittent cycle performance of the electrochemical device, the low-temperature rate performance, extrusion test pass rate and hot box test pass rate of the electrochemical device can be effectively improved, and the high-temperature anti-extrusion performance and hot box safety performance of the electrochemical device are improved, thereby improving the safety performance of the electrochemical device.

[0015] In some embodiments of the present application, the isolation film includes a bonding layer, and the longest diameter of the bonding points in the bonding layer is 20 μm to 380 μm. 1 When the value of is within the above range, the isolation membrane and the positive electrode sheet have better adhesion, so that the electrochemical device has better structural stability and high-temperature anti-extrusion performance, and at the same time has better low-temperature rate performance at high current density.

[0016] In some embodiments of the present application, the isolation film includes a bonding layer, and the distance between two adjacent bonding points in the bonding layer is 120 μm to 300 μm. 2 When the value of is within the above range, the adhesion between the isolation membrane and the positive electrode is further improved, so that the electrochemical device has better structural stability and high-temperature anti-extrusion performance, and at the same time has better low-temperature rate performance at high current density.

[0017] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good performance.

[0018] Beneficial effects of this application:

[0019] The present application provides an electrolyte, an electrochemical device and an electronic device. The electrolyte comprises lithium bis(fluorosulfonyl)imide and a fluorinated compound. Based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the fluorinated compound is B%, 0.3≤A≤2, 0.5≤B≤2.5. The bis(fluorosulfonyl)imide anion in the electrolyte (FSI - Anions) and fluorinated compounds can form a stable microscopic chemical structure with the highest occupied molecular orbital (high HOMO orbital energy level). When the value of A and the value of B are regulated within the scope of the present application, a relatively dense and thin positive electrode solid electrolyte interface film (CEI film) can be formed at a uniform rate on the surface of the positive electrode active material during the charge and discharge process of the electrochemical device. This structure can reduce the content of hydrogen fluoride gas formed by side reactions at the positive electrode interface and reduce the thickness expansion of the electrochemical device, thereby improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0020] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0022] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of electrochemical devices to explain the present application, but the electrochemical devices of the present application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0023] The first aspect of the present application provides an electrolyte, which includes lithium bis(fluorosulfonyl)imide (LiFSI) and a fluorinated compound, wherein the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the fluorinated compound is B%, 0.3≤A≤2, 0.5≤B≤2.5 based on the mass of the electrolyte. For example, the value of A can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or a range consisting of any two of the values; the value of B can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, or a range consisting of any two of the values. When the value of A or the value of B is too large (greater than the upper limit of this application), the viscosity of the electrolyte is relatively large, which is not conducive to the thickness uniformity of the CEI film formed at the interface between the positive electrode plate and the electrolyte. When the thickness of the CEI film is uneven, it will lead to different electrolyte circulation speeds, which will increase the side reactions in the local area and increase the byproducts of the reaction between the electrolyte and some positive electrode active materials, thereby deteriorating the high-temperature storage performance and low-temperature intermittent cycle performance of the electrochemical device. When the value of A or the value of B is too small (less than the lower limit of this application), the stability of the CEI film formed during the charge and discharge process is poor, and it is difficult to form a relatively uniform CEI film, resulting in expansion of the electrochemical device and increased gas production. The bis(fluorosulfonyl)imide anion (FSI) in the electrolyte - Anions) and fluorinated compounds can form a stable microscopic chemical structure with the highest occupied molecular orbital (high HOMO orbital energy level). When the values ​​of A and B are adjusted within the scope of this application, a relatively dense and thin positive electrode solid electrolyte interface film (CEI film) can be formed at a uniform rate on the surface of the positive electrode active material during the charge and discharge process of the electrochemical device. This structure can reduce the content of hydrogen fluoride gas formed by side reactions at the positive electrode interface and reduce the thickness expansion of the electrochemical device, thereby improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device. In this application, high temperature here refers to a temperature ≥40°C, and low temperature here refers to a temperature ≤0°C.

[0024] In some embodiments of the present application, 0.45≤A≤1.2. For example, the value of A can be 0.45, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2 or a range consisting of any two of these values. When the electrolyte includes lithium bis(fluorosulfonyl)imide and satisfies the value of A within the scope of the present application, it is beneficial to further form a CEI film of suitable thickness on the surface of the positive electrode active material, and the stability of the positive electrode interface can be maintained during the subsequent redox reaction, that is, the oxidative decomposition of the electrolyte solvent at the positive electrode interface and the generation of HF gas are reduced, and the corrosion of the positive electrode active material by the acidic gas is reduced, thereby improving the chemical stability of the positive electrode active material, thereby reducing the thickness expansion of the electrochemical device, and then improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0025] In some embodiments of the present application, 1.2≤B≤2.0. For example, the value of B can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or a range consisting of any two of these values. When the electrolyte includes a fluorinated compound and satisfies the value of B within the scope of the present application, it is beneficial to further form a CEI film of suitable thickness on the surface of the positive electrode active material, and the stability of the positive electrode interface can be maintained during the subsequent redox reaction, that is, the oxidative decomposition of the electrolyte solvent at the positive electrode interface and the generation of HF gas are reduced, and the corrosion of the positive electrode active material by the acidic gas is reduced, thereby improving the chemical stability of the positive electrode active material, thereby reducing the thickness expansion of the electrochemical device, and then improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0026] In some embodiments of the present application, 0.12≤A / B≤2.0. For example, the value of B / A can be 0.12, 0.2, 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, or a range consisting of any two of these values. When the electrolyte includes lithium bis(fluorosulfonyl)imide and a fluorinated compound, and the value of B / A is within the range of the present application, the bis(fluorosulfonyl)imide anion FSI in the electrolyte is - Anions and cyclic fluorinated carbonates can form a stable microstructure with high HOMO orbital energy levels, further enabling FSI - The CEI film with a more suitable thickness formed between the anions and the fluorinated compounds on the surface of the positive electrode active material can maintain the stability of the positive electrode interface during the subsequent redox reaction, that is, reduce the oxidative decomposition of the electrolyte solvent at the positive electrode interface and the generation of HF gas, and reduce the corrosion of the positive electrode active material by the acidic gas, thereby improving the chemical stability of the positive electrode active material, thereby further reducing the thickness expansion of the electrochemical device, and further improving the high-temperature storage performance and low-temperature intermittent cycle performance of the electrochemical device.

[0027] In some embodiments of the present application, the electrolyte further comprises a dinitrile compound and a trinitrile compound, and based on the mass of the electrolyte, the mass percentage of the dinitrile compound is C%, the mass percentage of the trinitrile compound is D%, 1.53≤C / D≤2.4, 1.50≤D≤2.35. For example, the value of C / D can be 1.53, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or a range consisting of any two of the values; the value of D can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.35, or a range consisting of any two of the values. A dinitrile compound is a compound containing two cyano groups, and a trinitrile compound is a compound containing three cyano groups. When the electrolyte includes dinitrile compounds and trinitrile compounds and satisfies the values ​​of C / D and D within the scope of the present application, the dinitrile compounds and the trinitrile compounds will produce a certain synergistic effect within the scope. Since the electron cloud distributions of the dinitrile compounds and the trinitrile compounds are different, it is beneficial to form a relatively uniform CEI film on the surface of the positive electrode. The combination of the two makes the CEI film have multiple chemical properties and a certain chemical reaction inertness, thereby reducing the occurrence of chemical side reactions in the electrolyte and reducing the generation of by-products; on the other hand, it is beneficial to improve the voltage drop of the electrochemical device at high temperature and improve the structural stability of the electrochemical device at high temperature, thereby further improving the safety performance while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0028] In some embodiments of the present application, 2.295≤C≤5.64. For example, the value of C can be 2.295, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 5.64, or a range consisting of any two of these values. When the electrolyte includes a dinitrile compound and satisfies the value of C within the scope of the present application, it is beneficial to improve the voltage drop of the electrochemical device at high temperature and improve the structural stability of the electrochemical device at high temperature, thereby improving the safety performance while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0029] In the present application, the dinitrile compound may include but is not limited to at least one of adiponitrile, succinonitrile, ethylene glycol di(2-cyanoethyl) ether, glutaronitrile or 1,4-dicyano-2-butene; the trinitrile compound may include but is not limited to at least one of 1,3,6-hexanetrinitrile, 1,2,6-hexanetrinitrile or 1,3,5-pentanetrinitrile.

[0030] In some embodiments of the present application, the electrolyte further comprises propyl propionate, and the mass percentage of propyl propionate is 32% to 39% based on the mass of the electrolyte. For example, the mass percentage of propyl propionate can be 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or a range consisting of any two of the values. When propyl propionate is included in the electrolyte and the mass percentage of propyl propionate is within the range of the present application, the risk of increasing the AC impedance value of the electrochemical device under high temperature conditions can be reduced, and propyl propionate contributes to FSI. - Anions and fluorinated compounds form a more uniform LiF-containing negative electrode solid electrolyte membrane (SEI membrane) at the negative electrode interface. This structure has a good stabilizing function of reducing the formation of lithium dendrites, which can effectively reduce the generation of acidic gases during the cycle, thereby improving the high-temperature storage performance, low-temperature intermittent cycle performance and safety performance of the electrochemical device.

[0031] In some embodiments of the present application, the fluorinated compound includes at least one of fluoroethylene carbonate (FEC), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate or 4,4-difluoro-5,5-dimethylethylene carbonate. By selecting fluorinated compounds within the above-mentioned range, the electrolyte can have a lower viscosity and a higher lithium ion conductivity, which is beneficial to the migration of ions in the electrolyte; at the same time, it is more conducive to the formation of a stable and relatively uniform SEI film at the interface between the negative electrode plate and the electrolyte, further reducing the side reactions of the electrolyte, reducing the gas production at the positive electrode interface and the negative electrode interface, making the positive electrode interface and the negative electrode interface have better interface stability, reducing the influence of gas molecules on the positive electrode interface and the negative electrode interface, thereby improving the low-temperature intermittent cycle performance and high-temperature storage performance of the electrochemical device.

[0032] In some embodiments of the present application, the fluorinated compound includes at least one of fluoroethylene carbonate (FEC) or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. By selecting the fluorinated compound within the above-mentioned range, the electrolyte can have a lower viscosity and a higher lithium ion conductivity, which is beneficial to the migration of ions in the electrolyte; at the same time, it also helps the formation of the SEI film, further reduces the side reactions of the electrolyte, and makes the positive electrode interface and the negative electrode interface have better interface stability, thereby further improving the low-temperature intermittent cycle performance and high-temperature storage performance of the electrochemical device.

[0033] In some embodiments of the present application, the electrolyte further includes 4-isopropylphenyl diphenyl phosphate, and the mass percentage of 4-isopropylphenyl diphenyl phosphate is M%, based on the mass of the electrolyte, and 1.5≤M≤4.5. For example, the value of M can be 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or a range consisting of any two of these values. When 4-isopropylphenyl diphenyl phosphate is included in the electrolyte and the value of M is within the range of the present application, it is beneficial to form a denser and more uniform SEI film at the negative electrode interface, reduce the solvent decomposition of the electrolyte during the reduction process, and reduce the risk of lithium dendrites deposited on the surface of the negative electrode, thereby further improving the high temperature storage performance, low temperature intermittent cycle performance and safety performance of the electrochemical device.

[0034] In other embodiments of the present application, the electrolyte may also include at least one of vinyl sulfate (DTD) or vinylene sulfate (VC), and may further include at least one of fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0035] In some other embodiments of the present application, in addition to LiFSI, the electrolyte further includes an ionizable lithium salt, and the ionizable lithium salt includes LiPF 6 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiN(C 2 F 5 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 or LiC 4 BO 8At least one of. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, and is preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less. By regulating the concentration of the ionizable lithium salt within the above range, the number of mobile lithium ions in the electrolyte is large, and the viscosity of the electrolyte is moderate, so that the electrolyte impedance is low and the lithium ion migration rate is fast, thereby improving the performance of the electrochemical device.

[0036] In other embodiments of the present application, the electrolyte further comprises at least one of fluoroether, fluoroethylene carbonate or ether solvent. In other embodiments of the present application, the electrolyte may further comprise a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0037] The carbonate compound may include not only a chain carbonate compound, but also a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0038] The linear carbonate compound can include diethyl carbonate (DEC), ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. The example of cyclic carbonate compound is ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. The example of fluorinated carbonate compound is 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0039] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0040] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0041] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0042] The second aspect of the present application provides an electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte in any of the foregoing embodiments. The positive electrode sheet and the negative electrode sheet are separated by a separator disposed between them. In some embodiments, the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, the positive electrode material layer may include a positive electrode active material and a first compound, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, and the negative electrode material layer may include a negative electrode active material. Therefore, the electrochemical device of the present application has good high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance and safety performance.

[0043] In some embodiments of the present application, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the specific surface area of ​​the positive electrode active material is 0.3 m 2 / g to 0.4m 2 / g. For example, the specific surface area of ​​the positive electrode active material can be 0.3m 2 / g, 0.32m 2 / g, 0.34m 2 / g, 0.36m 2 / g, 0.38m 2 / g, 0.4m 2 / g or a range consisting of any two of the above values. By regulating the specific surface area of ​​the positive electrode active material within the above range, the positive electrode sheet has an active surface area and mechanical strength adapted to the electrolyte of the present application, while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device, the low temperature rate performance, extrusion test pass rate and hot box test pass rate of the electrochemical device can be effectively improved, and the high temperature anti-extrusion performance and hot box safety performance of the electrochemical device are improved, thereby improving the safety performance of the electrochemical device.

[0044] In the present application, the specific surface area of ​​the positive electrode active material is regulated by means known to those skilled in the art, as long as the purpose of the present application can be achieved. For example, the specific surface area of ​​the positive electrode active material can be regulated by mechanical crushing. Exemplarily, the mechanical crushing method can be ball milling or the like. Generally, the specific surface area increases with increasing ball milling time, and decreases with shortening ball milling time. The specific surface area of ​​the positive electrode active material can also be regulated by selecting a positive electrode active material of suitable particle size. The larger the particle size of the positive electrode active material, the smaller the specific surface area of ​​the positive electrode active material, and the smaller the particle size of the positive electrode active material, the larger the specific surface area of ​​the positive electrode active material.

[0045] In some embodiments of the present application, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a first compound, the first compound includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate, based on the mass of the positive electrode material layer, the mass percentage of the first compound is F ppm, and the surface density of the positive electrode material layer is E mg / cm 2 , 93≤F / E≤560, 500≤F≤2800. For example, the value of F / E can be 93, 100, 150, 180, 185, 200, 250, 300, 350, 400, 450, 500, 560, or a range consisting of any two of them; the value of F can be 500, 800, 1000, 1300, 1500, 1800, 2000, 2300, 2500, 2800, or a range consisting of any two of them. By regulating the values ​​of F / E and F within the above range, the positive electrode plate has good wetting characteristics adapted to the electrolyte of the present application, and the positive electrode plate and the electrolyte work synergistically. While taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device, the low temperature rate performance, extrusion test pass rate and hot box test pass rate of the electrochemical device can be effectively improved, the high temperature anti-extrusion performance and hot box safety performance of the electrochemical device are improved, thereby improving the safety performance of the electrochemical device.

[0046] In some embodiments of the present application, 185≤F / E≤560. For example, the value of F / E can be 185, 200, 250, 300, 350, 400, 450, 500, 550, 560 or a range consisting of any two of these values. By regulating the value of F / E within the above range, the positive electrode plate has good wetting characteristics adapted to the electrolyte of the present application, and the positive electrode plate and the electrolyte work synergistically, while taking into account the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device, the low temperature rate performance, extrusion test pass rate and hot box test pass rate of the electrochemical device can be further improved, and the high temperature anti-extrusion performance and hot box safety performance of the electrochemical device are improved, thereby improving the safety performance of the electrochemical device.

[0047] In some embodiments of the present application, 0.89≤E≤30.1. For example, the value of E can be 0.89, 1, 5, 10, 15, 20, 25, 30, 30.1 or a range consisting of any two of these values. By regulating the value of F / E within the above range, the positive electrode sheet has excellent wetting characteristics adapted to the electrolyte of the present application, which can further improve the low-temperature rate performance, extrusion test pass rate and hot box test pass rate of the battery, improve the high-temperature anti-extrusion performance and hot box safety performance of the electrochemical device, thereby improving the safety performance of the electrochemical device.

[0048] In the present application, the surface density of the positive electrode material layer is regulated by means known to those skilled in the art, as long as the purpose of the present application can be achieved. For example, when the positive electrode slurry is coated on the surface of the positive electrode current collector, on the basis of a certain coating weight per unit area of ​​the positive electrode material layer, the surface density of the positive electrode material layer can be increased by increasing the solid content of the positive electrode slurry, and the thickness of the positive electrode material layer can be reduced by reducing the solid content of the positive electrode slurry; on the basis of a certain solid content of the positive electrode slurry, the surface density of the positive electrode material layer can be increased by increasing the coating weight per unit area of ​​the positive electrode material layer, and the coating weight per unit area of ​​the positive electrode material layer can be reduced to reduce the surface density of the positive electrode material layer.

[0049] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector. The positive electrode material layer may be located on one side or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may be made of aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 200 μm. In some embodiments, the positive electrode material layer may be coated only on a partial area of ​​the positive electrode current collector. In some embodiments, the thickness of the positive electrode material layer may be 20 μm to 490 μm, and further preferably, the thickness may be 20 μm to 400 μm, and further, it may be 40 μm to 120 μm, and further, it may be 40 μm to 90 μm.

[0050] In some embodiments, as described above, the positive electrode material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. Further preferably, the positive electrode active material is lithium cobalt oxide or lithium iron phosphate.

[0051] In some embodiments, at least part of the surface of the positive electrode material layer is provided with a covering layer, the covering layer includes lithium phosphate and / or lithium niobate, the mass ratio of the two substances is 1:3 to 1:1, and the thickness of the covering layer is 1 μm to 1.8 μm. Through the above arrangement, the positive electrode sheet has better conductivity and makes the structure of the positive electrode active material more stable, which is conducive to improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0052] In some embodiments, the positive electrode plate further includes a first material layer, and the first material layer is located between the positive electrode material layer and the positive electrode current collector. The first material layer includes lithium dihydrogen phosphate or aluminum dihydrogen phosphate, and the mass percentage of lithium dihydrogen phosphate or aluminum dihydrogen phosphate is W%, 5≤W≤20 based on the total mass of the first material layer. Through the above arrangement, the positive electrode plate has better conductivity and makes the physical and chemical structure of the positive electrode active material more stable, which is conducive to improving the high temperature storage performance and low temperature intermittent cycle performance of the electrochemical device.

[0053] In some embodiments, the positive electrode material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0054] In some embodiments of the present application, the isolation film includes a bonding layer, and the longest diameter D of the bonding points in the bonding layer is 1 For example, the longest diameter D of the bonding point in the bonding layer is 20 μm to 380 μm. 1 It can be 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 380 μm or a range consisting of any two of these values. By regulating the longest diameter of the bonding point in the bonding layer within the above range, the separator and the positive electrode sheet have better adhesion, so that the electrochemical device has better structural stability and high temperature anti-extrusion performance, and at the same time has better low temperature rate performance at high current density.

[0055] In some embodiments of the present application, the isolation film includes a bonding layer, and the distance D between two adjacent bonding points in the bonding layer is 2 For example, the distance D between two adjacent bonding points is 120 μm to 300 μm. 2It can be 120 μm, 150 μm, 180 μm, 210 μm, 240 μm, 270 μm, 300 μm or a range consisting of any two of these values. By regulating the distance between two adjacent bonding points within the above range, the bonding between the separator and the positive electrode is further improved, so that the electrochemical device has better structural stability and high temperature anti-extrusion performance, and at the same time has better low temperature rate performance at high current density.

[0056] In some embodiments of the present application, the bonding layer includes a binder and a thickener. The binder includes but is not limited to at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyvinyl alcohol, and sodium carboxymethyl cellulose. The thickener includes but is not limited to at least one of hydroxyethyl cellulose, methyl hydroxyethyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, or sodium alginate. The present application has no particular restrictions on the content of the binder in the bonding layer and the content of the thickener in the bonding layer, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.

[0057] In some embodiments, the substrate of the isolation film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film as a whole is in the range of about 3 μm to 480 μm.

[0058] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a porous layer binder, the inorganic particles are selected from alumina (Al 2 O 3 ), silicon oxide (SiO 2 ), magnesium oxide (MgO), titanium oxide (TiO 2 ), hafnium dioxide (HfO 2 ), tin oxide (SnO 2 ), cerium dioxide (CeO 2 ), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The porous layer binder is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece. One surface of the isolation membrane may also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer, and the high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes a cycloolefin copolymer. Based on the mass of the polyolefin porous substrate, the mass percentage z of the high temperature resistant resin is 2.5% to 9%. For example, the mass percentage z of the high temperature resistant resin is 2.5%, 3%, 5%, 7%, 8%, 9% or a range consisting of any two of these values. When the above-mentioned type of high temperature resistant resin is added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is controlled within the above range, it is beneficial to increase the melting point of the isolation membrane, improve the isolation membrane strength and the high temperature storage performance of the electrochemical device.

[0059] The present application has no particular restrictions on the preparation method of the isolation membrane, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to the following steps: (1) mixing a binder and a thickener evenly to obtain a bonding layer slurry; (2) mixing inorganic particles and a porous layer binder evenly to obtain a ceramic coating slurry; (3) coating the ceramic coating slurry on one surface of the substrate of the isolation membrane, and after drying, forming a ceramic coating on one surface of the substrate, coating the bonding layer slurry on the surface of the ceramic coating away from the substrate, and after drying, obtaining an isolation membrane with a single-sided coating of the ceramic coating and the bonding layer; (4) repeating the above steps on the other surface of the substrate to obtain the isolation membrane.

[0060] In this application, the longest diameter D of the bonding point in the bonding layer is 1 The adjustment can be carried out by means known to those skilled in the art, as long as the purpose of the present application can be achieved. For example, when the adhesive layer of the isolation film is prepared by screen printing coating, the longest diameter D of the adhesive point in the adhesive layer can be adjusted by replacing the screen printing plate of different types. 1 The distance D between two adjacent bonding points in the bonding layer 2The adjustment can be carried out by means known to those skilled in the art, as long as the purpose of the present application can be achieved. For example, when the adhesive layer of the isolation film is prepared by screen printing coating, the distance D between two adjacent adhesive points in the adhesive layer can be adjusted by changing the mesh of the screen printing plate. 2 When the screen printing plate has a certain shape, the mesh size of the screen printing plate increases, and the longest diameter D of the bonding point in the bonding layer 2 The mesh size of the screen printing plate is reduced, and the longest diameter D of the bonding point in the bonding layer is reduced. 2 Increase.

[0061] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector. The negative electrode material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0062] In some embodiments, as described above, the negative electrode material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0063] In some embodiments, the negative electrode material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode material layer may be any other suitable material. In some embodiments, the mass ratio of the negative active material, the negative electrode conductor, and the negative electrode binder in the negative electrode material layer may be (80 to 99): (0.5 to 10): (0.5 to 10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0064] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0065] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0066] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device of the present application has good performance.

[0067] The present application does not specifically limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0068] Example

[0069] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0070] Test methods and equipment:

[0071] Sampling method for positive electrode sheets and positive active materials:

[0072] The lithium-ion battery discharged at 0.2C to 2.0V was disassembled, the positive electrode sheet was taken out, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then the positive electrode sheet was placed in an oven and baked at 80°C for 12 hours to obtain the treated positive electrode sheet sample. The positive electrode sheet samples in the following surface density test of the positive electrode material layer were sampled using the above method.

[0073] The positive electrode material layer on the positive electrode sheet was scraped off with a scraper, and the scraped powder was heat treated at 400°C for 4 hours in a tube furnace under argon protection to obtain a positive electrode active material powder sample. The positive electrode active material samples in the following specific surface area test of the positive electrode active material were sampled using the above method.

[0074] Surface density test of positive electrode material layer:

[0075] The positive electrode sample is punched into two small discs with a radius of 5 mm and an area of ​​S mm. 2 , weigh them one by one and take the average value, which is counted as a; wipe the positive electrode material layer on the small disc with deionized water, weigh them one by one and take the average value, which is counted as a 1 .

[0076] If the positive electrode sheet includes a single-sided positive electrode material layer, the surface density of the positive electrode material layer is E = (aa 1 ) / S, unit is mg / cm 2 .

[0077] If the positive electrode sheet includes a double-sided positive electrode material layer, the surface density of the positive electrode material layer is E = (aa 1 ) / 2S, unit is mg / cm 2 .

[0078] Specific surface area test of positive electrode active material:

[0079] The positive electrode active material samples were dried in a vacuum drying oven and placed in sample tubes. The specific surface area of ​​the positive electrode active material samples was tested by nitrogen adsorption / desorption method using a specific surface area analyzer (TristarⅡ3020M). The specific test was conducted in accordance with GB / T 19587-2017 Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method.

[0080] Test of the longest diameter of the bonding point and the distance between two adjacent bonding points:

[0081] The lithium-ion battery discharged to 2.0V at 0.2C was disassembled, and then the separator was taken out. The separator was soaked in N-methylpyrrolidone (NMP) for 30 minutes, and then dried at 25°C in a fume hood for 4 hours, and the dried separator was taken out.

[0082] At any position on the surface of the isolation film, select an area with a length of 3470μm and a width of 2600μm, use a CCD (Charge-coupled Device) electron microscope of model KEYENCE VHX5000, magnify 100 times and observe and record the image information of the area. The longest diameter of the bonding point in the area and the distance between two adjacent bonding points are tested as follows:

[0083] Select any 15 bonding points to measure the longest diameter (if it is a regular circle, it is the diameter; if it is not a circle, the distance between the two farthest endpoints is the longest diameter), and calculate the average value to obtain the longest diameter D of the bonding point. 1Select any two adjacent bonding points. If the shapes of the bonding points are regular (sphericity is 1) and the diameters are the same, measure the distance between the centers of the two circles. If they are irregular, record the two adjacent bonding points as bonding point X and bonding point Y. The line connecting the centers of the circumscribed circles of bonding point X and bonding point Y intersects the outline of bonding point X at X. 1 and X 2 , where X 1 Away from bonding point Y, X 2 Close to bonding point Y; the line connecting the centers of the circumscribed circles of bonding point X and bonding point Y intersects the contour of bonding point Y at Y 1 and Y 2 , where Y 1 Away from bonding point X, Y 2 Close to bonding point X; the distance between the two bonding points is X 1 Y 2 or X 2 Y 1 Select 10 groups of adjacent bonding points and calculate X 1 Y 2 or X 2 Y 1 The distance D between two adjacent bonding points is obtained by taking the average value of the length 2 .

[0084] -15℃ intermittent cycle 200 cycles capacity retention test:

[0085] At -15°C, the lithium-ion battery was allowed to stand for 30 minutes; it was charged to 4.5V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage of 4.5V; the lithium-ion battery was then allowed to stand in a -15°C environment for 24 hours; the lithium-ion battery was then discharged to 3.0V at a constant current of 0.5C, and the discharge capacity of the lithium-ion battery was recorded; this was a complete intermittent charge and discharge cycle, and the lithium-ion battery was charged and discharged 200 times in the same way.

[0086] Capacity retention rate after 200 intermittent cycles at -15°C (%) = discharge capacity at the 200th cycle / first discharge capacity × 100%.

[0087] Among them, the higher the capacity retention rate after 200 intermittent cycles at -15°C, the better the low-temperature intermittent cycle performance of the lithium-ion battery.

[0088] Storage capacity test after 10 days storage at 45°C:

[0089] At 25°C, the lithium-ion battery is charged at a constant current of 1C to a voltage of 4.45V, and then charged at a constant voltage of 4.45V to a current of 0.05C. After the lithium-ion battery reaches a fully charged state, the initial capacity of the lithium-ion battery is tested to be C. 0; Then put the lithium-ion battery into a constant temperature box at 45℃ and store it for 10 days. Then take out the test lithium-ion battery and the 1C discharge capacity is C 1 .

[0090] Capacity retention rate of lithium-ion battery after storage at 45°C for 10 days (%) = (C 1 / C 0 )×100%.

[0091] Among them, the higher the capacity retention rate of the lithium-ion battery after storage at 45°C for 10 days, the better the high-temperature storage performance of the lithium-ion battery.

[0092] High temperature side squeeze test:

[0093] At 45°C, charge at a constant current rate of 0.5C to 4.4V, then charge at a constant voltage of 4.4V to 0.05C. Adopt UL1642 test standard (lithium battery safety standard), and the side extrusion force is 13kN. Perform high temperature side extrusion test on lithium-ion batteries, and test 20 lithium-ion batteries in each group. If the lithium-ion battery does not smoke, catch fire or explode during the test, it is considered to have passed the test. The number of lithium-ion batteries that pass the test is X, then the high temperature side extrusion test pass rate of this group of lithium-ion batteries = X / 20.

[0094] Among them, the higher the pass rate of the high-temperature side extrusion test, the better the high-temperature anti-extrusion performance and the better the safety performance of the lithium-ion battery.

[0095] Low temperature rate performance test:

[0096] Take the lithium ion battery in the embodiment or comparative example to be tested and let it stand for 5 minutes at a test temperature of -10°C, then charge the lithium ion battery to 4.45V at a constant current of 0.7C, and then charge it to 0.05C at a constant voltage of 4.45V; let it stand for 5 minutes, then discharge it to 3.0V at a constant current of 0.2C, and record the 0.2C discharge capacity; then let it stand for 5 minutes, repeat the above charging process, and then discharge it at a constant current of 2C, and record the 2C discharge capacity.

[0097] Low temperature rate capacity retention rate (%) = 2C discharge capacity / 0.2C discharge capacity × 100%.

[0098] Among them, the higher the low-temperature rate capacity retention rate, the better the low-temperature rate performance of the lithium-ion battery.

[0099] Electrolyte component test:

[0100] The electrolyte components were tested using a gas chromatography-mass spectrometer (GC-MS, model: Agilent GC 7890A), and the external standard method was used to test the components to measure the mass percentage of each component in the electrolyte.

[0101] 140℃ hot box test pass rate test:

[0102] (1) The prepared lithium-ion battery was charged at a constant current of 0.5C to a cut-off voltage of 4.2V, then charged at a constant voltage of 4.2V to a cut-off current of 200mA, and then allowed to stand for 5 minutes;

[0103] (2) Attach a temperature-sensitive wire to the fully charged lithium-ion battery between the two pole ears, connect the two pole ears to monitor the voltage, and hang the lithium-ion battery vertically in the box;

[0104] (3) The temperature of the hot box was raised to 140°C at a rate of 5°C / min and maintained at that temperature for 60 min.

[0105] Each group tests 20 lithium-ion batteries. The judging criteria are: the lithium-ion batteries pass if they do not catch fire or explode. Count the number of lithium-ion batteries that pass the hot box test.

[0106] 140°C hot box test pass rate (%) = number of lithium-ion batteries that passed the hot box test / 20×100%.

[0107] Among them, the higher the 140°C hot box test pass rate, the better the hot box safety performance and the better the safety performance of the lithium-ion battery.

[0108] Example 1-1

[0109] <Preparation of positive electrode sheet>

[0110] The positive electrode active material is lithium cobalt oxide (LiCoO 2 ), conductive agent Super-P, binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, and then the first compound polybutyl acrylate is added, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, it is dried under vacuum conditions at 120°C for 1h to obtain a positive electrode sheet with a size of 74mm (width) × 854mm (length) with a current collector empty foil area at the tail. Among them, the specific surface area of ​​the positive active material is 0.3m 2 / g, the mass percentage content F of the first compound is 2800ppm, the thickness of the single-sided positive electrode material layer after cold pressing is 90μm, and the surface density E of the positive electrode material layer is 30mg / cm 2 .

[0111] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0112] <Preparation of negative electrode sheet>

[0113] The negative electrode active material artificial graphite, conductive agent conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are mixed in a weight ratio of 96.5:1.5:1:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 75wt%. The negative electrode slurry is evenly coated on one side of the negative electrode collector copper foil, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The above steps are repeated on the other side of the negative electrode collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 76mm (width) × 874mm (length) is obtained. Among them, the unit area coating weight of the single-sided negative electrode material layer is 90mg / 1540.25mm 2 The thickness of the single-sided negative electrode material layer after cold pressing is 90μm.

[0114] <Preparation of Electrolyte>

[0115] In a glove box filled with argon, ethylene carbonate (EC) is first heated at a high temperature of 60° C. to convert it into a liquid state, and then EC: dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) is prepared as a basic solvent in a mass ratio of 1:1:1, propyl propionate and a fluorinated compound fluoroethylene carbonate (FEC) are added, and then solid lithium hexafluorophosphate is added to prepare a 1.1 mol / L lithium hexafluorophosphate solution by a constant volume method, and solid LiFSI accounting for 0.3% of the total mass of the electrolyte is added, that is, the value of A is 0.3; finally, adiponitrile and 1,3,6-hexanetrinitrile are added, so that the mass content of adiponitrile accounts for 3.6% of the total mass of the entire electrolyte, the mass content of 1,3,6-hexanetrinitrile accounts for 2% of the total mass of the entire electrolyte, fluoroethylene carbonate accounts for 1% of the total mass of the electrolyte, and propyl propionate accounts for 32% of the total mass of the electrolyte, that is, the value of B is 1, the value of C is 3.6, the value of D is 2, and the balance is the basic solvent.

[0116] <Preparation of Separator Film>

[0117] A 10 μm thick polyethylene (PE) microporous membrane was selected as the substrate of the isolation membrane. Inorganic particles of boehmite with a Dv50 of 1.3 μm were mixed with polyacrylate in a mass ratio of 88:12 and dissolved in deionized water to form a ceramic coating slurry with a solid content of 43%. The binder polyvinylidene fluoride and the thickener sodium carboxymethyl cellulose were mixed in a mass ratio of 98.5:1.5, deionized water was added as a solvent, and the mixture was stirred evenly to form a bonding layer slurry with a solid content of 75 wt%.

[0118] Subsequently, the obtained ceramic coating slurry is evenly coated on one side of the substrate by a micro-concave coating method, and dried in an oven to obtain a ceramic coating with a thickness of 1.8 μm. The bonding layer slurry is coated on the surface of the ceramic coating away from the substrate by a screen printing coating method, wherein the longest diameter of the sieve plate is 100 μm and the mesh is 100 mesh. After drying at 60°C, an isolation membrane with a single-sided coating of a ceramic coating and an adhesive layer is obtained; thereafter, the above steps are repeated on the other surface of the substrate to obtain an isolation membrane. The coating weight per unit area of ​​the ceramic coating is 0.8 g / m 2 The coating weight per unit area of ​​the adhesive layer is 0.55 g / m 2 .

[0119] <Preparation of lithium-ion batteries>

[0120] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ears, the electrode assembly is placed in an outer packaging aluminum-plastic film, and after dehydration at 80°C, the above-mentioned electrolyte is injected, and after vacuum packaging, standing, formation, shaping, capacity testing and other processes, a lithium-ion battery is obtained.

[0121] Example 1-2 to Example 1-6

[0122] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1. Among them, when the value of A in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0123] Example 1-7 to Example 1-15

[0124] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1. When the value of B in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0125] Example 1-16 to Example 1-23

[0126] Except that the value of D is adjusted according to Table 1, the value of C / D changes accordingly, and the rest is the same as Example 1-1. Among them, when the value of D in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0127] Example 1-24 Example 1-28

[0128] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1. When the mass percentage of propyl propionate in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0129] Examples 1-29

[0130] Except for adding 4-isopropylphenyl diphenyl phosphate in <Preparation of electrolyte> and adjusting relevant parameters according to Table 1, the rest is the same as Example 1-1. Among them, when 4-isopropylphenyl diphenyl phosphate in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0131] Example 1-30 to Example 1-34

[0132] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-29. Among them, when the value of M in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0133] Example 1-35 to Example 1-42

[0134] Except for adjusting the type of fluorinated compound according to Table 1, the rest is the same as Example 1-1.

[0135] Embodiment 1-43

[0136] Except that the dinitrile compound, trinitrile compound and propyl propionate are not added in <Preparation of the electrolyte> and the relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when the dinitrile compound, trinitrile compound and propyl propionate are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0137] Embodiment 1-44

[0138] Except that propyl propionate is not added in <Preparation of electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when propyl propionate is not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0139] Embodiment 1-45

[0140] Except that the dinitrile compound and the trinitrile compound are not added in <Preparation of the electrolyte> and the relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when the dinitrile compound and the trinitrile compound are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0141] Embodiment 1-46

[0142] Except that the dinitrile compound, trinitrile compound and propyl propionate are not added in <Preparation of the electrolyte> and the relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-30. Among them, when the dinitrile compound, trinitrile compound and propyl propionate are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0143] Example 2-1 to Example 2-39

[0144] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1. Among them, when the surface density E of the positive electrode material layer changes, the solid content of the positive electrode material layer slurry is adjusted so that the value of E is as shown in Table 2. When the mass percentage content F of the first compound changes, the mass ratio of the positive electrode active material to the first compound is adjusted so that the mass percentage content F of the first compound is as shown in Table 2. When the longest diameter D of the bonding point in the bonding layer 1 When changes occur, replace the screen printing plate with a different version so that the longest diameter D of the bonding point in the bonding layer 1 As shown in Table 2. When the distance D between two adjacent bonding points in the bonding layer 2 When the change occurs, adjust the mesh of the screen printing plate so that the distance D between two adjacent bonding points in the bonding layer 2 As shown in Table 2.

[0145] Example 3-1

[0146] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.

[0147] <Preparation of positive electrode sheet>

[0148] The positive electrode active material is lithium cobalt oxide LiCoO 2 , amorphous carbon as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and polybutyl acrylate as a first compound are mixed in a mass ratio of 96.75:1:2:0.25, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum stirrer to obtain a positive electrode slurry with a solid content of 65wt%; 2kg of lithium phosphate and lithium niobate are prepared in a mass ratio of 1:2, 0.1kg of conductive carbon and 10kg of deionized water are added, and the mixture is stirred at a stirring speed of 1300rpm for 2.5h to obtain a covering layer slurry with a solid content of 65wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, the aluminum foil is dried at 120°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side, the covering layer slurry is coated on the other surface of the positive electrode material layer away from the aluminum foil, and the positive electrode sheet is dried at 120°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer and a covering layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer and a covering layer. Then, after cold pressing, cutting, and welding the pole ears, dry it under vacuum conditions at 120°C for 1 hour to obtain a positive electrode sheet with a size of 74mm (width) × 867mm (length) and a current collector empty foil area at the tail. The coating weight per unit area of ​​the single-sided positive electrode material layer is 250mg / 1540.25mm 2 After cold pressing, the thickness T of the positive electrode sheet excluding the covering layer is 60 μm, and the thickness of the single-sided covering layer is 1.5 μm.

[0149] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0150] Example 3-2 to Example 3-3

[0151] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-1.

[0152] Embodiment 3-4

[0153] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.

[0154] <Preparation of positive electrode sheet>

[0155] 4.2545 kg of lithium dihydrogen phosphate, 3 kg of polyacrylic acid, 28 kg of boehmite and 0.2 kg of conductive carbon were added into 60 kg of deionized water and stirred at a stirring speed of 1300 rpm for 2.5 h to obtain a first material layer slurry with a solid content of 24 wt%; the positive electrode active material lithium cobalt oxide LiCoO 2 , conductive agent amorphous carbon, binder polyvinylidene fluoride (PVDF), and the first compound polybutyl acrylate are mixed in a mass ratio of 96.75:1:2:0.25, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The first material layer slurry is coated on a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 120°C to obtain a positive electrode current collector coated with the first material layer on one side, and the positive electrode slurry is coated on the other surface of the first material layer away from the aluminum foil, and dried at 120°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer and a first material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer and a first material layer on both sides. After cold pressing, cutting, and welding the tabs, the cathode sheet was dried at 120°C for 1 hour to obtain a cathode sheet with a size of 74 mm (width) × 867 mm (length) with a current collector blank at the tail. The coating weight per unit area of ​​the single-sided cathode material layer is 250 mg / 1540.25 mm 2 After cold pressing, the thickness T of the positive electrode sheet excluding the first material layer is 60 μm, the thickness of the single-sided first material layer is 1.5 μm, and based on the mass of the first material layer, the mass percentage W of lithium dihydrogen phosphate is 12%.

[0156] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0157] Example 3-5 to Example 3-7

[0158] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-4. When the mass percentage of lithium dihydrogen phosphate changes, the amount of lithium dihydrogen phosphate added is adjusted so that the value of W is as shown in Table 3.

[0159] Comparative Examples 1 to 7

[0160] Except that the value of A and the value of B are adjusted according to Table 1, and the value of A / B changes accordingly, the rest is the same as Example 1-1. Among them, when the values ​​of A and B in the electrolyte change, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0161] Comparative Example 8

[0162] Except that no fluorinated compound is added in <Preparation of electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when no fluorinated compound is added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0163] Comparative Example 9

[0164] Except that lithium bis(fluorosulfonyl)imide is not added in <Preparation of Electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. When lithium bis(fluorosulfonyl)imide is not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0165] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.

[0166] Table 1

[0167]

[0168]

[0169] Note: “ / ” in Table 1 indicates no relevant preparation parameters.

[0170] From Examples 1-1 to 1-46 and Comparative Examples 1 to 9, it can be seen that when the electrolyte includes lithium bis(fluorosulfonyl)imide and fluorinated compounds, and the values ​​of A and B are within the scope of this application, the high-temperature storage capacity retention rate and low-temperature intermittent cycle retention rate of the lithium-ion battery are high, indicating that the lithium-ion battery of this application has good high-temperature storage performance and low-temperature intermittent cycle performance. The values ​​of A and B in the electrolytes of Comparative Examples 1 to 7 are outside the scope of this application; there are no fluorinated compounds in the electrolyte of Comparative Example 8; there is no lithium bis(fluorosulfonyl)imide in the electrolyte of Comparative Example 9; the high-temperature storage capacity retention rate and low-temperature intermittent cycle retention rate of the lithium-ion battery in Comparative Examples 1 to 9 are low, indicating that the lithium-ion battery of this application has good high-temperature storage performance and low-temperature intermittent cycle performance.

[0171] The value of A / B usually affects the high temperature storage performance and low temperature intermittent cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-15 that when the value of A / B is within the scope of the present application, the high temperature storage capacity retention rate and low temperature intermittent cycle retention rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance and low temperature intermittent cycle performance.

[0172] The value of C and the value of C / D usually affect the high temperature storage performance, low temperature intermittent cycle performance and safety performance of the lithium ion battery. It can be seen from Examples 1-1, 1-16 to 1-23 that when the value of C and the value of C / D are within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate and 140°C hot box test pass rate of the lithium ion battery are high, indicating that the lithium ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance and safety performance.

[0173] The mass percentage of propyl propionate usually affects the high temperature storage performance, low temperature intermittent cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-24 to 1-28 that when the mass percentage of propyl propionate is within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance and safety performance.

[0174] The value of M usually affects the high temperature storage performance, low temperature intermittent cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-29 to 1-34 that when the value of M is within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance and safety performance.

[0175] The type of fluorinated compound usually affects the high temperature storage performance and low temperature intermittent cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 and 1-35 to 1-42 that when the type of fluorinated compound is within the scope of the present application, the high temperature storage capacity retention rate and low temperature intermittent cycle retention rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance and low temperature intermittent cycle performance.

[0176] Different combinations of electrolytes usually affect the high temperature storage performance, low temperature intermittent cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 1-1 to 1-46 that when the combination of electrolytes is within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance and safety performance.

[0177]

[0178]

[0179] The specific surface area of ​​the positive electrode active material usually affects the high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-1 to 2-4, and 2-25 that when the specific surface area of ​​the positive electrode active material is within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate, high temperature extrusion test pass rate, low temperature rate capacity retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance.

[0180] The value of F, the value of E and the value of F / E usually affect the high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance of the lithium ion battery. It can be seen from Examples 1-1, 2-5 to 2-22 and 2-25 that when the value of F, the value of E and the value of F / E are within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate, high temperature extrusion test pass rate, low temperature rate capacity retention rate and 140°C hot box test pass rate of the lithium ion battery are high, indicating that the lithium ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance.

[0181] D 1The value of D usually affects the high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-23 to 2-32 that when D 1 The values ​​of are within the scope of the present application, and the high-temperature storage capacity retention rate, low-temperature intermittent cycle retention rate, high-temperature extrusion test pass rate, low-temperature rate capacity retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high-temperature storage performance, low-temperature intermittent cycle performance, low-temperature rate performance, high-temperature anti-extrusion performance and hot box safety performance.

[0182] D 2 The value of usually affects the high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-33 to 2-38, and 2-25 that when D 2 The values ​​of are within the scope of the present application, and the high-temperature storage capacity retention rate, low-temperature intermittent cycle retention rate, high-temperature extrusion test pass rate, low-temperature rate capacity retention rate and 140°C hot box test pass rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high-temperature storage performance, low-temperature intermittent cycle performance, low-temperature rate performance, high-temperature anti-extrusion performance and hot box safety performance.

[0183] The type of the first compound usually affects the high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance of the lithium ion battery. It can be seen from Examples 1-1 and 2-39 that when the type of the first compound is within the scope of the present application, the high temperature storage capacity retention rate, low temperature intermittent cycle retention rate, high temperature extrusion test pass rate, low temperature rate capacity retention rate and 140°C hot box test pass rate of the lithium ion battery are high, indicating that the lithium ion battery of the present application has good high temperature storage performance, low temperature intermittent cycle performance, low temperature rate performance, high temperature anti-extrusion performance and hot box safety performance.

[0184] Table 3

[0185]

[0186] Note: " / " in Table 3 indicates no relevant preparation parameters. "Lithium phosphate: lithium niobate = 1:2" in Example 3-1 means that the mass ratio of lithium phosphate to lithium niobate is 1:2. The same applies to other examples.

[0187] The coating layer on the surface of the positive electrode material layer usually affects the high temperature storage performance and low temperature intermittent cycle performance of the lithium-ion battery. It can be seen from Example 1-1, Example 3-1 to Example 3-3 that when the various parameters of the coating layer on the surface of the positive electrode material layer are within the scope of the present application, the high temperature storage capacity retention rate and low temperature intermittent cycle retention rate of the lithium-ion battery are high, indicating that the lithium-ion battery of the present application has good high temperature storage performance and low temperature intermittent cycle performance.

[0188] The content of lithium dihydrogen phosphate or aluminum dihydrogen phosphate in the positive electrode material layer usually affects the high temperature storage performance and low temperature intermittent cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 3-4 to 3-7 that when the value of W is within the scope of the present application, the high temperature storage capacity retention rate and low temperature intermittent cycle retention rate of the lithium ion battery are high, indicating that the lithium ion battery of the present application has good high temperature storage performance and low temperature intermittent cycle performance.

[0189] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0190] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0191] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte comprising lithium bis(fluorosulfonyl)imide and a fluorinated compound, wherein the mass percentage of the lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the fluorinated compound is B%, and 0.3≤A≤2, 0.5≤B≤2.5 based on the mass of the electrolyte.

2. The electrolyte according to claim 1, wherein 0.45≤A≤1.2。 3. The electrolyte according to claim 1, wherein 1.2≤B≤2.0。 4. The electrolyte according to claim 1, wherein 0.12≤A / B≤2.

0.

5. The electrolyte according to claim 1, wherein The electrolyte further includes a dinitrile compound and a trinitrile compound. Based on the mass of the electrolyte, the mass percentage of the dinitrile compound is C%, and the mass percentage of the trinitrile compound is D%, 1.53≤C / D≤2.4, 1.50≤D≤2.

35.

6. The electrolyte according to claim 1, wherein The electrolyte further comprises propyl propionate, and based on the mass of the electrolyte, the mass percentage of propyl propionate is 32% to 39%.

7. The electrolyte according to claim 1, wherein The fluorinated compound includes at least one of fluoroethylene carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate or 4,4-difluoro-5,5-dimethylethylene carbonate.

8. The electrolyte according to claim 7, wherein The fluorinated compound includes at least one of fluoroethylene carbonate or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

9. The electrolyte according to claim 1, wherein The electrolyte also includes 4-isopropylphenyl diphenyl phosphate. Based on the mass of the electrolyte, the mass percentage of 4-isopropylphenyl diphenyl phosphate is M%, and 1.5≤M≤4.

5. 10 . An electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to claim 1 .

11. The electrochemical device according to claim 10, wherein: The positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, and the specific surface area of ​​the positive electrode active material is 0.3 m 2 / g to 0.4m 2 / g.

12. The electrochemical device according to claim 10, wherein: The positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a first compound, the first compound includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate, based on the mass of the positive electrode material layer, the mass percentage of the first compound is F ppm, and the surface density of the positive electrode material layer is E mg / cm 2 , 93≤F / E≤560, 500≤F≤2800.

13. The electrochemical device according to claim 12, wherein: 185≤F / E≤560.

14. The electrochemical device according to claim 10, wherein: The isolation film includes an adhesive layer, and the longest diameter of the adhesive points in the adhesive layer is 20 μm to 380 μm.

15. The electrochemical device according to claim 10, wherein: The isolation film includes a bonding layer, and a distance between two adjacent bonding points in the bonding layer is 120 μm to 300 μm.

16. An electronic device comprising the electrochemical device according to any one of claims 10 to 15.